Jaw musculature of the Picini (Aves: Piciformes: Picidae) - Donatelli, Reginaldo José [UNESP] (Hindawi, 2012)
The Picini tribe comprises 25 Old World woodpecker species grouped into seven genera that are widely distributed in Asia and include several representatives from the Eurasian region. Given the absence of detailed anatomical studies of Picini in the literature, the purposes of this study were to describe the jaw musculature of 14 species of Picini in detail and to compare the musculature patterns of these species. The results of this analysis indicate the following: (1) there is a clear association between the ventralis lateralis and dorsalis lateralis muscles through fleshy fibers that are connected in all species, (2) the jaw musculature of the genus Picus differs from that of other Picini genera in terms of the poor development of the protractor muscle system of the quadrate (M. protractor quadrati and M. protractor pterygoidei), (3) generally, the M. pseudotemporalis superficialis originates in the ventrocaudal region of the laterosphenoid (the lower part of the orbit), with the only noteworthy exception being an origin in the upper part of the orbit in Dinopium javanense, and (4) the protractor pterygoidei muscle is more developed in Blythipicus rubiginosus, Dinopium rafflesii, and D. javanense than in the other species. © 2012 Reginaldo José Donatelli.
Keywords: Aves; Blythipicus rubiginosus; Dinopium javanense; Dinopium rafflesii; Picidae; Piciformes; Picus